2019
DOI: 10.3390/brainsci9110326
|View full text |Cite
|
Sign up to set email alerts
|

EEG Emotion Classification Using an Improved SincNet-Based Deep Learning Model

Abstract: Deep learning (DL) methods have been used increasingly widely, such as in the fields of speech and image recognition. However, how to design an appropriate DL model to accurately and efficiently classify electroencephalogram (EEG) signals is still a challenge, mainly because EEG signals are characterized by significant differences between two different subjects or vary over time within a single subject, non-stability, strong randomness, low signal-to-noise ratio. SincNet is an efficient classifier for speaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…For example, in the analysis of frontal EEG measurements of 174 patients in ICU, a deep learning model could predict the level of consciousness (AUC of 0.70) and delirium with (AUC of 0.80). An EEG signal can be used for epileptic focus localization [23], emotion classification [24], and detection of psychotic disorders such as unipolar depression [25] with high reliability, if AI is adopted.…”
Section: Recent Cases Of Application Of Ai To Biosignals In Medicinementioning
confidence: 99%
“…For example, in the analysis of frontal EEG measurements of 174 patients in ICU, a deep learning model could predict the level of consciousness (AUC of 0.70) and delirium with (AUC of 0.80). An EEG signal can be used for epileptic focus localization [23], emotion classification [24], and detection of psychotic disorders such as unipolar depression [25] with high reliability, if AI is adopted.…”
Section: Recent Cases Of Application Of Ai To Biosignals In Medicinementioning
confidence: 99%
“…We use eeglab toolbox in Matlab to pre-process and process EEG data. A band-pass filter is employed to keep EEG signals with a frequency range between 1 and 30 Hz for fatigue driving analysis [ 36 ], independent component analysis (ICA) [ 28 , 37 ] is used for removing EOG artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…Zheng [83]. In [92], Zeng et al used an architecture that adapted from Sinc-Net (a CNN-based network proposed for speaker recognition [93]) to classify emotion. Their results demonstrated that the adapted SincNet (i.e., three convolutional layers and three fully connected layers) was promising for emotion classification, reaching an accuracy of around 95% as evaluated on the SEED dataset.…”
Section: Emotion Recognitionmentioning
confidence: 99%
“…A prominent advance we need to mention is the EEGNet [54], which is proven effective for different BCI paradigms. Another promising model is SincNet, which was initially proposed for speaker recognition and also well for the classification of EEG signal [92]. New deep learning architectures, such as capsule network [38], are also required to enhance the chance of success of EEG applications.…”
Section: Wu Et Al Utilized Both Eeg and Electrooculogram (Eog) To Classify The Level Of Vigilance By Fusing The Features Extracted From Ementioning
confidence: 99%